Development of Powtoon-Based Learning Media For Pancasila Education In Grade IV Elementary Schools - Yunia, Khanifa Intan; Reinita, Reinita; Nisa, Sahrun; Waldi, Atri (Papanda Publisher, 2025)
The limited use of engaging and varied learning media in Indonesian elementary schools has resulted in conventional teacher-centered learning patterns, particularly affecting subjects requiring active engagement such as Pancasila Education. This study aimed to develop valid, practical, and effective Powtoon-based learning media for fourth-grade Pancasila Education using systematic instructional design principles. This Research and Development study employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) across three elementary schools in Padang City, Indonesia. The research involved 69 fourth-grade students and utilized expert validation questionnaires, teacher and student practicality assessments, and pre-test/post-test measures to evaluate media quality and learning effectiveness. Data analysis employed descriptive statistics and N-Gain calculations. Expert validation yielded an overall score of 89.3% (